The Success of Information System in Small and Medium Enterprises - Sri Dewi Anggadini; Deden A Wahab; Dedi Sulistiyo Soegoto (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was to determine how increased organizational culture, management support, and internal control affected the success of accounting information systems in Small Medium Enterprices’. The technique used is descriptive and verification technique with a quantitative approach. The pattern uses 30 pattern small and medium organizations that become carried out accounting records systems. The analytical method used is multiple linear regression analysis, and the T-test is used to test the hypothesis partially. This study shows that organizational culture has a significant influence on the success of accounting information system. The support of top management has a significant influence on the success of accounting information system. Internal control has a significant influence on the success of an accounting information system. The better the organizational culture must have top management support and internal control, the better the current accounting information system. The results are expected to provide solutions or solve problems related to accounting information systems that are not available, not on time, and experiencing issues in carrying out their functions so that the accounting information system is not optimal. Through this research, it can also be useful to provide an overview and proof that the success of an accounting information system is influenced by many factors so that these factors must be considered and improved in an effort to realize the goals of small and medium enterprises, namely to improve people’s welfare.